Primary endodontic infections - key issue in pathogenesis of chronic apical periodontitis - Alexandru Andrei Iliescu; Irina Maria Gheorghiu; Sergiu Ciobanu; Ion Roman; Anca Silvia Dumitriu; George Alexandru Denis Popescu; Stana Păunică (Journal of Mind and Medical Sciences)
Primary root canal infection is a dynamic process. All species of oral microbiota have comparable abilities to establish in the root canals of necrotic teeth. The essential ecological factors in their biological selection are nutrient availability, anaerobic environment and bacterial interactions. In chronic apical periodontitis, all selected microflora residing in the long-term infected habitat of root canals system are synergistic, and each of them can play the role of an endodontic pathogen. Microorganisms living in the root canal system of pulpless teeth progressively reach through anatomical communications to the periodontal ligament where, sooner or later, they cause the inflammatory and immunological conflict between the infection and the host. The insight into the complexity of the root canal microbiota is improved by the current pyrosequencing and next-generation sequencing diagnostic techniques, which allow the identification of multispecies of the microbiome and their targeted treatment. The insight into the complexity of root canal microbiota is improved by present diagnostic techniques of pyrosequencing and next generation sequencing, which allow the identification of multispecies of the microbiome and their targeted treatment.